Computer simulations of dislocations - Bulatov, Vasily V. (Oxford series on materials modelling, 2006)
The book presents a variety of methods for computer simulations of crystal defects in the form of ""numerical recipes"", complete with computer codes and analysis tools. By working through numerous case studies and problems, this book provides a useful starter kit for further method development in the computational materials sciences. - ;This book presents a broad collection of models and computational methods - from atomistic to continuum - applied to crystal dislocations. Its purpose is to help students and researchers in computational materials sciences to acquire practical knowledge of rel